Phytochemical characterization of Marula (Sclerocarya birrea) ethanolic leaf extract: A Precursor for Green Corrosion Inhibitor Development - Shathani, Phenyo; Ogunmuyiwa, Enoch Nifise; Obadele, Babatunde Abiodun; Oladijo, Oluseyi Philip (Sciences of Phytochemistry, 2025)
In the search for environmentally friendly corrosion inhibitors, medicinal plants rich in various phytochemicals present promising options due to their natural ability to adsorb onto metal surfaces, forming protective barriers against corrosive agents. This study examines the phytochemical profile of the ethanolic extract of Sclerocarya birrea using Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible (UV-Vis) spectroscopy, and Gas Chromatography-Mass Spectrometry (GC-MS). The UV-Vis spectrum displayed distinct absorption peaks characteristic of the extract’s components. FTIR analysis confirmed the presence of functional groups associated with alkanes, alkenes, phenols, amines, aromatics, esters, ketones, and aldehydes. GC-MS detected 17 phytochemical compounds, including notable components such as γ-sitosterol (39.44%), l-(+)-ascorbic acid 2,6-dihexadecanoate (17.37%), pagicerine (14.66%), hexadecanoic acid derivatives (10.45%), octadecanoic acid (4.34%), and phytol (3.46%). These compounds are known for their medicinal properties and chemical structures that support effective corrosion inhibition. The phytochemicals primarily contribute to corrosion protection by adsorbing onto metal surfaces, creating protective films that impede both anodic and cathodic reactions, thus reducing metal dissolution and increasing resistance. The detailed phytochemical analysis provides a solid basis for further research into S. birrea as a sustainable and effective corrosion inhibitor for various metals in different corrosive environments. This work emphasizes the extract’s potential as an environmentally friendly alternative to traditional synthetic inhibitors.